2023
DOI: 10.1021/acs.jafc.3c03186
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharides from Genistein-Stimulated Monascus purpureus Ameliorate Cyclophosphamide-Induced Intestinal Injury via PI3K/AKT-MAPKs/NF-κB Pathways and Regulation of Gut Microbiota

Liuming Xie,
Ting Chen,
Xin Qi
et al.

Abstract: Exopolysaccharides from genistein-stimulated Monascus purpureus (G-EMP) exhibited immunomodulatory potential in vitro, but whether it had immune-enhancing effects in vivo and its potential mechanism are not yet known. Here, the immunomodulatory effects of G-EMP were investigated by establishing an immunosuppressed mouse model treated with cyclophosphamide (Cy). The results suggested that G-EMP effectively alleviated the signs of weight reduction and diet reduction caused by Cy, increased fecal water content an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…However, the G-EMP treatment markedly reversed these changes. Oral administration of G-EMP did not affect the colonic intestinal structure of normal mice . Notably, the colon possesses two mucous layers, wherein the outer layer creates a unique ecological niche for colonizing gut microbiota, whereas the internal layer is resilient to bacteria .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the G-EMP treatment markedly reversed these changes. Oral administration of G-EMP did not affect the colonic intestinal structure of normal mice . Notably, the colon possesses two mucous layers, wherein the outer layer creates a unique ecological niche for colonizing gut microbiota, whereas the internal layer is resilient to bacteria .…”
Section: Discussionmentioning
confidence: 92%
“…However, it should be noted that some Bacteroides can damage the mucous membrane layers, which may aggravate colitis. , Our results indicated that the Bacteroides exhibited a negative correlation with ZO-1, occludin, and claudin, along with a positive correlation with IL-6 and IL-1β, as also described in a previous study . Furthermore, oral administration of G-EMP to normal mice enhanced the diversity of the gut microbiota and facilitated the growth of beneficial bacteria, demonstrating that G-EMP can effectively regulate the gut microbiota, thereby assisting in maintaining of intestinal health . Meanwhile, our previous study demonstrated that 5-ASA had a modulating property on the gut microbiota of DSS mice, but the effect was lower than that of polysaccharides .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Monascus purpureus supplementation ameliorates NAFLD induced by high-fat, high-fructose, and high-cholesterol diet, 39 and genistein-stimulated Monascus purpureus can enhance beneficial bacteria such as Lactobacillus , showing a positive correlation with most immunological indicators. 40 Lichtheimia ramosa , an opportunistic fungal pathogen of the order Mucorales, 41 was found to be mostly over-proliferated in patients with low immune function. 20 In our study, fecal Lichtheimia ramosa was substantially increased in NASH mice, and was largely eliminated by B. uniformis and B. bifidum .…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal microbiota profoundly influences intestinal homeostasis, not only affecting intestinal metabolites but also regulating intestinal immune homeostasis [ 31 ]. The study of alpha and beta indices were analysed herein, with the results showing that PNF, PNS, and PNP increased the homology and diversity of microorganisms in the cecum, with low doses of PNS being the most effective.…”
Section: Discussionmentioning
confidence: 99%